“Traditions vs Innovations: Possibility of Necessary - Necessity of Possible”: IX Meeting of Interdisciplinary Scientific Discussion Club - O. A. Moskvitina (Научный диалог)
The announcement of scientific event is presented. On February 15, 2017 the Psychological Institute of the Russian Academy of Education organizes IX meeting of the interdisciplinary scientific discussion club “Traditions vs Innovations: Possibility of Necessary - Necessity of Possible.”